Lanthanide diphosphonates based on a V-shaped ligand: syntheses, structures, experimental and theoretical luminescence properties1. Issue 40 (28th October 2015) - Tang, Si-Fu; Li, Xuebing
<x xml:space="preserve">Abstract</x> Four lanthanide diphosphonates were synthesized from a V-shaped ligand and structurally characterized. Both experimental and theoretical photoluminescence properties were investigated.